2015
DOI: 10.1371/journal.pone.0125610
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Hyaluronic Acid Gel after Intrauterine Surgery May Improve Spontaneous Fertility: A Randomized Controlled Trial in New Zealand White Rabbits

Abstract: ObjectiveIntrauterine adhesions (IUAs) are the most common complication after hysteroscopy in patients of reproductive age. Intra-abdominal anti-adhesion gel reduces the incidence of adhesions, but effects on fertility after uterine surgery are not known. The objective of our work was to evaluate the effect of intrauterine anti-adhesion gel on spontaneous fertility after repeated intrauterine surgery with induced experimental synechiae in the rabbit model.Materials and MethodsTwenty New Zealand White rabbits u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Some investigators found the mechanical damage to the endometrium could reduce the endometrial glandular epithelium and increase the collagen fibers in animal model of artificial abortion [19], leading to the increased proportion of collagen fibers in the endometrium. There is evidence showing that the increased collagen fibers in the organ may significantly compromise the elasticity of this organ and increases its stiffness [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators found the mechanical damage to the endometrium could reduce the endometrial glandular epithelium and increase the collagen fibers in animal model of artificial abortion [19], leading to the increased proportion of collagen fibers in the endometrium. There is evidence showing that the increased collagen fibers in the organ may significantly compromise the elasticity of this organ and increases its stiffness [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A further study using animal models supported these findings. Huberlant et al (21) performed bilateral uterine curettage in 20 New Zealand white rabbits where one uterine tube in each rabbit was its own control. The rabbits were randomized into two groups where the second uterine tube was treated with either hyaluronic acid or isotonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal model of intrauterine adhesions, Huberlant et al [19] showed that the use of hyaluronic acid gel immediately after dilatation and curettage significantly improved fertility, and significantly reduced the incidence of intrauterine adhesions. Acunzo et al [20] randomly divided 132 patients into two groups.…”
Section: Discussionmentioning
confidence: 99%